2023
DOI: 10.3390/jcm12062412
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor Ligands and Receptors in Breast Cancer

Abstract: Breast cancer (BC) is the most common malignancy responsible for the largest number of deaths in women worldwide. The risk of developing BC is predisposed by many factors such as age, presence of genetic mutations or body weight. The diagnosis is mostly made relatively late, which is why patients are exposed to radical surgical treatments, long-term chemotherapy and lower survival rates. There are no sufficiently sensitive and specific screening tests; therefore, researchers are still looking for new diagnosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 101 publications
0
7
0
Order By: Relevance
“…The current study shows a positive correlation between pre-treatment AOPPs and VEGF-A, which could be evidence of a relationship between oxidative protein damage in breast cancer and excessive angiogenic process. The role of VEGF in pathological angiogenesis in malignant tumours is essential [ 60 ]. Interestingly, the current study shows that lower pre-treatment levels of sVEGFR1 and lower post-treatment levels of sVEGFR2 were related to elevated levels of post-treatment AOPPs.…”
Section: Discussionmentioning
confidence: 99%
“…The current study shows a positive correlation between pre-treatment AOPPs and VEGF-A, which could be evidence of a relationship between oxidative protein damage in breast cancer and excessive angiogenic process. The role of VEGF in pathological angiogenesis in malignant tumours is essential [ 60 ]. Interestingly, the current study shows that lower pre-treatment levels of sVEGFR1 and lower post-treatment levels of sVEGFR2 were related to elevated levels of post-treatment AOPPs.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, our results showed that pro-tumorigenic cytokines were reduced in CIRP/PyMT mice when compared to PyMT mice at both early and late time points. Interestingly, an assessment of the cytokines produced by mammary glands with early lesions showed significantly lower levels of VEGF-A, whose role in angiogenesis in breast cancer is well established [75,76]. CIRP was also recently shown to negatively regulate angiogenesis in vivo [77].…”
Section: Discussionmentioning
confidence: 99%
“…IL-10 downregulates the expression of Th1-type cytokines and increases the immune tolerance of cancer in the tumor microenvironment [62][63][64], while IL-1β is associated with an increased risk for bone metastasis in human breast cancer [78]. LIF was shown to promote migration and metastasis in breast cancer through the AKT-mTOR pathway [54], and elevation of VEGF-A in breast cancer is typically associated with poor prognosis and higher rates of metastasis [75,76]. IL-6 is known to promote invasiveness through epithelial-to-mesenchymal transition and is associated with the formation and maintenance of breast cancer stem cells [67].…”
Section: Discussionmentioning
confidence: 99%
“…In a state of hypoxia, VEGF-A is secreted by a variety of cells, including tumor cells, macrophages, platelets, dendritic cells, astrocytes, and osteoblasts [66]. VEGF-A is secreted into several isoforms with different biological properties through alternative splicing of mRNA, and the dominant isoform is VEGF165 [67]. In EVs studies, Ko and colleagues found that VEGF189 was preferentially enriched in small EVs that were secreted by cancer cells [32], and Feng and colleagues identified a unique 90 kDa form of VEGF on the surface of breast cancer cell-derived microvesicles [68].…”
Section: Discussionmentioning
confidence: 99%